Copepod carcasses in the subtropical convergence zone of the Sargasso Sea: implications for microbial community composition, system respiration and carbon flux. (2nd September 2019) - Tang, Kam W; Backhaus, Liv; Riemann, Lasse; Koski, Marja; Grossart, Hans-Peter; Munk, Peter; Nielsen, Torkel Gissel
Abstract: The oligotrophic subtropical gyre covers a vast area of the Atlantic Ocean. Decades of time-series monitoring have generated detailed temporal information about zooplankton species and abundances at fixed locations within the gyre, but their live/dead status is often omitted, especially in the dynamic subtropical convergence zone (STCZ) where the water column stratification pattern can change considerably across the front as warm and cold water masses converge. We conducted a detailed survey in the North Atlantic STCZ and showed that over 85% of the copepods were typically concentrated in the upper 200 m. Copepod carcasses were present in all samples and their proportional numerical abundances increased with depth, reaching up to 91% at 300–400 m. Overall, 14–19% of the copepods within the upper 200 m were carcasses. Shipboard experiments showed that during carcass decomposition, microbial respiration increased, and the bacterial community associated with the carcasses diverged from that in the ambient water. Combining field and experimental data, we estimated that decomposing copepod carcasses constitute a negligible oxygen sink in the STCZ, but sinking carcasses may represent an overlooked portion of the passive carbon sinking flux and should be incorporated in future studies of carbon flux in this area.